Joseph Loxton Rawbon, the "Master Restorer" - Cyndie Lack (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Joseph Loxton Rawbon arrived in Canada during the intense commercial and industrial growth of the Victorian era.  A colourful character with bombastic flair, his numerous enterprises, however limited in their success, exemplify the boundless optimism of the Industrial Age and open a small window onto the history of Toronto's early cultural development through to the Second World War.  Remarkably, Rawbon believed that, like his artist's stretchers and other inventions, the restoration of paintings held a key to the making of a fortune.